The Role of the Environment in Eliciting Phantom-Like Sensations in Non-Amputees - Lewis, Elizabeth; Lloyd, Donna M.; Farrell, Martin J. (Frontiers in Psychology, 2013)
Following the amputation of a limb, many amputees report that they can still vividly perceive its presence despite conscious knowledge that it is not physically there. However, our ability to probe the mental representation of this experience is limited by the intractable and often distressing pain associated with amputation. Here, we present a method for eliciting phantom-like experiences in non-amputees using a variation of the rubber hand illusion in which a finger has been removed from the rubber hand. An interpretative phenomenological analysis revealed that the structure of this experience shares a wide range of sensory attributes with subjective reports of phantom limb experience. For example, when the space where the ring finger should have been on the rubber hand was stroked, 93% of participants (i.e., 28/30) reported the vivid presence of a finger that they could not see and a total of 57% (16/28) of participants who felt that the finger was present reported one or more additional sensory qualities such as tingling or numbness (25%; 7/28) and alteration in the perceived size of the finger (50%; 14/28). These experiences indicate the adaptability of body experience and share some characteristics of the way that phantom limbs are described. Participants attributed changes to the shape and size of their ‘missing’ finger to the way in which the experimenter mimed stroking in the area occupied by the missing finger. This alteration of body perception is similar to the phenomenon of telescoping experienced by people with phantom limbs and suggests that our sense of embodiment not only depends on internal body representations but on perceptual information coming from peripersonal space.